Anti-allergic effect of Aster yomena on ovalbumin-sensitized mouse and RHL-2H3 cells via Th1/Th2 cytokine balance. (May 2018) - Hwang, Kyung-A; Hwang, Yu-Jin; Song, Jin
Highlights: Aster yomena extracts inhibit the production of IgE and histamine in OVA-induced mice. Aster yomena extracts suppressed Th2 cytokines and increased Th1 cytokines production in OVA-induced mice. Aster yomena extracts reduced the number of Th2 cells and increased the number of Th1 cells. Aster yomena extracts inhibit the secretion of β-hexosaminidase of RBL-2H3 cells. Aster yomena extracts exerted anti-allergy activity. Abstract: Recently, the incidence of allergies is increasing worldwide. Immunoglobulin E (IgE)-mediated hypersensitivity is central to the pathogenesis of asthma, and other allergic diseases. Aster yomena (AY) have been valued for their medical properties including anti-inflammation, anti-pyresis and analgesia properties. In this study, we investigated the anti-allergic effects of AY and isoquercitrin, a functional compound of AY, using a mouse allergy model and cells. In mice with ovalbumin (OVA)-induced allergic rhinitis, oral administration of AY or isoquercitrin reduced secretion of IgE and histamine in the plasma. AY or isoquercitrin regulated both Th1 and Th2 cytokines levels in the plasma. In addition, AY and isoquercitrin showed dose-dependent inhibition of β-hexosaminidase and reduction in mRNA levels of Th2 cytokines in RBL-2H3 cells. Thus, our results demonstrate that AY or isoquercitrin suppresses cytokine production of the allergy response pathway, resulting in prevention or alleviation of allergy symptoms.